Effects of AKD Sizing on the Morphology and Pore Distribution Properties of OCC Fibers. (9th October 2019) - Chen, Hua; Yang, Jing; Hu, Zhijun; Zheng, Bingbing; Sun, Jun; Wo, Qizhong; Zeng, Xiangzhi; Qiu, Xufeng; Song, Chenying; Zhu, Ruifeng
Abstract : Changes of the morphology and pore structure of old corrugated container (OCC) fibers during an alkyl ketene dimer (AKD) sizing process were studied. The resulting samples were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), contact angle, and BET surface area analysis. The length of fibers had obvious influence on the AKD sizing effect, and the length of fibers ranged from 100 to 200 meshes showed the best sizing performance. The surface roughness of 0.3% AKD sizing OCC fibers decreased from 27.949 nm to 12.811 nm. Compared with the control sample, the pore volume of fibers sized with 0.1% AKD decreased 4.3% when the average pore diameter was fixed at 2.4~3.0 nm. And when the usage of AKD increased to 0.3% and 0.5%, the pore volume decreased 1.4% and 6.3% accordingly. The decrease in the pore volume of AKD-sized fiber indicated the penetration and deposition of dispersed particles of AKD in the fiber lumens.